Beauty – A Brief Conceptual Journey - Seel, Martin (Aesthetic Investigations, 2015)
The first part of the essay deals with four dimensions of aesthetic attraction in an attempt to provide a notion of beauty that is rich and robust enough to apply to different sorts and objects of aesthetic praise, including the productions of modern and contemporary arts. The second part confronts this apology of beauty with a number of test cases such as the ugly, the horrible and the sublime, including a discussion of putative couterexamples such as the films of Michael Haneke and the novels of Imre Kertész.